2018
DOI: 10.1002/jbio.201800087
|View full text |Cite
|
Sign up to set email alerts
|

easySLM‐STED: Stimulated emission depletion microscopy with aberration correction, extended field of view and multiple beam scanning

Abstract: We demonstrate a simplified set-up for STED microscopy with a straightforward alignment procedure that uses a single spatial light modulator (SLM) with collinear incident excitation and depletion beams to provide phase modulation of the beam profiles and correction of optical aberrations. We show that this approach can be used to extend the field of view for STED microscopy by correcting chromatic aberration that otherwise leads to walk-off between the focused excitation and depletion beams. We further show ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 22 publications
1
22
0
Order By: Relevance
“…When combined with iSIM imaging, an expansion factor of ∼4 results in an effective resolution of ∼140 / 4 = 35 nm laterally and ∼350 / 4 ≈ 90 nm axially after deconvolution. Compared with current state-of-the-art super-resolution microscopes with similar resolution performance, such as the HT-STORM 10 capable of imaging a 100×100 µm 2 FOV in ∼5-10 minutes or a similar FOV with easySLM-STED 32 in 60-80 minutes, the iSIM is capable of stitching together images of expanded samples to form an equivalent FOV within 2-5 seconds. This represents a 100-1000-fold improvement in imaging throughput.…”
Section: Resultsmentioning
confidence: 99%
“…When combined with iSIM imaging, an expansion factor of ∼4 results in an effective resolution of ∼140 / 4 = 35 nm laterally and ∼350 / 4 ≈ 90 nm axially after deconvolution. Compared with current state-of-the-art super-resolution microscopes with similar resolution performance, such as the HT-STORM 10 capable of imaging a 100×100 µm 2 FOV in ∼5-10 minutes or a similar FOV with easySLM-STED 32 in 60-80 minutes, the iSIM is capable of stitching together images of expanded samples to form an equivalent FOV within 2-5 seconds. This represents a 100-1000-fold improvement in imaging throughput.…”
Section: Resultsmentioning
confidence: 99%
“…Holograms were calculated using an adapted Direct Search (DS) approach, optimising the hologram on a pixel‐by‐pixel basis (Görlitz et al ., ). Computationally, the amplitude at any point in the focal plane ε(r2false) can be calculated as the sum of the contributions from the N pixels in the plane of the SLM (Curtis et al ., ): truerightεfalse(rfalse)=lefti=0NA0ρiexpiϕρiKr2false,ρi2falseleftprefixexp()i2πr·ρiλf,where A0false(ρ2falseifalse) and φ(ρi) denote the amplitude and phase of the light incident on the i th pixel on the SLM at a point ρ and λ is the wavelength of the light and f is focal length of the optical train.…”
Section: Methodsmentioning
confidence: 99%
“…Holograms were calculated using an adapted Direct Search (DS) approach, optimising the hologram on a pixel-by-pixel basis (Görlitz et al, 2018). Computationally, the amplitude at any point in the focal plane ( r ) can be calculated as the sum of the contributions from the N pixels in the plane of the SLM (Curtis et al, 2002):…”
Section: Hologram Calculationmentioning
confidence: 99%
“…Finally, the impact of tilt, which in this situation corresponds to a misalignment between excitation and depletion foci, is useful to be assessed to estimate the impact of chromatic aberrations [27] or thermal and mechanical drift [13]. We found that 2D-STED was the most sensitive to tilt, followed by z-STED and CH-STED, which can be linked to the respective sizes of their central areas, with a smaller central area leading to a higher vulnerability to misalignment (Figure 7(f)).…”
Section: Figure 7: Effect Of Common Aberrations On the Depletion Pattmentioning
confidence: 99%